Endoscopic suturing for mucosal defect closure following endoscopic submucosal dissection: Systematic review and meta-analysis - Niu, Chengu; Zhang, Jing; Farooq, Umer; Zahid, Salman; Okolo, Patrick I (Endoscopy International Open, 2024)
Background and study aims: Endoscopic submucosal dissection (ESD) is a minimally invasive and effective treatment for gastrointestinal lesions. It carries potential risks such as bleeding and perforation. This meta-analysis was conducted to assess the safety, effectiveness, and feasibility of endoscopic suturing, a promising technique for closing mucosal defects post-ESD.Methods: We reviewed several databases, including MEDLINE/PubMed, Cochrane Library, Web of Science, and Embase up to May 1,2023. We aimed at identifying original studies that provided insightful data on the use of endoscopic suturing in reducing complications post-ESD.Results: In our study, we evaluated 426 publications and included 10 studies involving a total of 284 patients. The pooled technical success rate of endoscopic suturing was 92.6% (95% confidence interval [CI] 0.88–0.96). The pooled rate for sustained closure of mucosal defects post-endoscopic submucosal dissection (ESD) was estimated to be 80.7% (95% CI 0.71–0.88). The pooled mean time required to perform the endoscopic suturing procedure was calculated to be 31.11 minutes (95% CI 16.01–46.21). Among the studies reviewed for the incidence of delayed perforation post-ESD, a singular event of perforation was documented, suggesting a minimal occurrence. The overall rate of delayed bleeding was 5.3% (95% CI 0.30–0.10). Within the subset of patients using antithrombotic drugs, our subgroup analysis identified a delayed bleeding event rate of 6.7% (95% CI 0.02–0.25).Conclusions: Our results underscore the potential of endoscopic suturing as a viable and efficient technique in managing mucosal defects following ESD, highlighting the need for further large, prospective research to corroborate these findings and concentrate on establishing standard methodologies.
Keywords: Endoscopy Upper GI Tract; Endoscopic resection (ESD, EMRc, ...); Endoscopy Lower GI Tract; Endoscopic resection (polypectomy, ESD, EMRc, ...); GI surgery